A taxonomy of conscientious objection in healthcare. (March 2022) - Gamble, Nathan; Saad, Toni
Conscientious Objection (CO) has become a highly contested topic in the bioethics literature and public policy. However, when CO is discussed, it is almost universally referred to as a single entity. Reality reveals a more nuanced picture. Healthcare professionals may object to a given action on numerous grounds. They may oppose an action because of its ends, its means, or because of factors that lay outside of both ends and means. Our paper develops a taxonomy of CO, which makes it possible to describe the refusals of healthcare professional with greater finesse. The application of this development will potentially allow for greater subtlety in public policy and academic discussions – some species of CO could be permitted while others could be prohibited.